A systematic review on gender dysphoria in adolescents and young adults: focus on suicidal and self-harming ideation and behaviours - Elisa Marconi; Laura Monti; Angelica Marfoli; Georgios D. Kotzalidis; Delfina Janiri; Cecilia Cianfriglia; Federica Moriconi; Stefano Costa; Chiara Veredice; Gabriele Sani; Daniela Pia Rosaria Chieffo (Child and Adolescent Psychiatry and Mental Health, 2023)
Abstract Introduction Gender dysphoria (GD) is characterized by the incongruence between one’s experienced and expressed gender and assigned-sex-at-birth; it is associated with clinically significant distress. In recent years, the number of young patients diagnosed with GD has increased considerably. Recent studies reported that GD adolescents present behavioural and emotional problems and internalizing problems. Furthermore, this population shows a prevalence of psychiatric symptoms, like depression and anxiety. Several studies showed high rates of suicidal and non-suicidal self-injurious thoughts and behaviour in GD adolescents. To increase understanding of overall mental health status and potential risks of young people with GD, this systematic review focused on risk of suicide and self-harm gestures. Methods We followed the PRISMA 2020 statement, collecting empirical studies from four electronic databases, i.e., PubMed, Scopus, PsycINFO, and Web of Science. Results Twenty-one studies on GD and gender nonconforming identity, suicidality, and self-harm in adolescents and young adults met inclusion criteria. Results showed that GD adolescents have more suicidal ideation, life-threatening behaviour, self-injurious thoughts or self-harm than their cisgender peers. Assessment methods were heterogeneous. Conclusion A standardised assessment is needed. Understanding the mental health status of transgender young people could help develop and provide effective clinical pathways and interventions.